The Effects of Old Age on Hepatic Stellate Cells. (2nd May 2011) - Warren, Alessandra; Cogger, Victoria C.; Fraser, Robin; DeLeve, Laurie D.; McCuskey, Robert S.; Le Couteur, David G.
Abstract : Aging is associated with marked changes in the hepatic sinusoid, yet the effect of old age on hepatic stellate cells (HSC) has not been well described. Transmission electron microscopy and immunohistochemistry were used to study the effects of aging on HSC in livers from rats (3-4 mths versus 24–27 mths) and mice (2-3 mths versus 20–22 mths). Desmin-positive HSC doubled in old age in both mice and rats. Alpha-smooth muscle actin- ( α SMA-) positive cells did not increase significantly and remained only a small percentage of desmin-positive cells. Electron microscopy revealed that old age is associated with HSC that have a substantial increase in the number of lipid droplets which are larger in diameter. There was also a marked increase of HSC that protruded into the sinusoidal lumen in old mice. In conclusion, old age is associated with hyperplasia of HSC that are not activated and are engorged with lipid droplets.